2016
DOI: 10.18632/oncotarget.7898
|View full text |Cite
|
Sign up to set email alerts
|

Cinobufagin inhibits tumor growth by inducing intrinsic apoptosis through AKT signaling pathway in human nonsmall cell lung cancer cells

Abstract: The cinobufagin (CB) has a broad spectrum of cytotoxicity to inhibit cell proliferation of various human cancer cell lines, but the molecular mechanisms still remain elusive. Here we observed that CB inhibited the cell proliferation and tumor growth, but induced cell cycle arrest and apoptosis in a dose-dependent manner in non-small cell lung cancer (NSCLC) cells. Treatment with CB significantly increased the reactive oxygen species but decreased the mitochondrial membrane potential in NSCLC cells. These effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 57 publications
2
48
0
Order By: Relevance
“…Numerous studies showed that apoptosis or a reciprocal action between apoptosis and autophagy is the major process to control cell fates [8,9,12,24,25]. Interestingly, the findings of this study showed that bufadienolides KB, KA, and BC do not induce cellular apoptosis but only induced cell autophagy.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Numerous studies showed that apoptosis or a reciprocal action between apoptosis and autophagy is the major process to control cell fates [8,9,12,24,25]. Interestingly, the findings of this study showed that bufadienolides KB, KA, and BC do not induce cellular apoptosis but only induced cell autophagy.…”
Section: Discussionmentioning
confidence: 57%
“…Cinobufagin induced intrinsic apoptosis through AKT signaling pathway in human non-small cell lung cancer cells, including A549, H1299, H460, and SK-MES-1 [12]. In the clinical cases, 40% of patients suffer from a stage III or IV of non-small cell lung cancer, pancreatic cancer or hepatocellular carcinoma maintained a stable disease with the treatment of bufadienolidescontaining toad venom [13].…”
Section: Introductionmentioning
confidence: 99%
“…Excessive generation of ROS leads to oxidative damage to the mitochondrial membrane and, ultimately, triggers a series of mitochondrial associated events, including apoptosis [19, 20]. In view of the cinobufagin results showing that ROS generation is induced in A549/H1299 and HepG2 cells [9, 21], the ROS levels of U2OS and 143B cells were also detected after cinobufagin treatment. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cinobufagin (Fig. 1A) is a primary and active components of Chan-su [8, 9]. Cinobufagin is reported to have anti-tumor effects in various types of cancer, such as non-small cell lung cancer, colorectal cancer, hepatocellular carcinoma, breast cancer and prostate cancer [9-14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation